Analysis of Elementary School Students’ Literacy Ability of Javanese Script Through the Use of Script Card Reviewed Based on Critical Thinking Skills - Matsuri Matsuri; Idam Ragil Widianto Atmojo; Chumdari Chumdari; Fadhil Purnama Adi; Roy Ardiansyah; Dwi Yuniasih Saputri; Annisa Rahma Pradesiwi (STAI Hubbulwathan Duri, 2023)
Javanese script is very important for students to learn and understand, because Javanese script is a local wisdom culture that must be preserved in order to protect the nation's language culture so that it does not become extinct through the use of regional languages such as the use of Javanese script as a means for carrying out verbal and written communication and as a cultural expression.The aims of this study were: (1) to analyze the increase in Javanese script literacy skills and (2) to describe the increase in Javanese script literacy in terms of critical thinking skills. This is mixed methods research with a sequential explanatory strategy. The research sample consisted of fifth-grade students from Tegalsari Public Elementary School and Mangkuyudan Public Elementary School. Data gathering was conducted through the utilisation of tests, interviews, and documentation. From the findings and deliberation, the researchers are able to deduce the subsequent conclusions: (1) The proficiency in Javanese script among fifth-grade students in elementary schools improves following the implementation of script media by teachers. (2) Proficiency in critical thinking is closely correlated with the ability to read and write in Javanese script. The amount of critical thinking skills accounts for 39.3% of the variation in students' literacy skills in Javanese script, leaving 60.7% to be attributed to other factors. Students who possess advanced proficiency in Javanese script literacy exhibit a pronounced inclination towards critical thinking. Students who possess a moderate level of proficiency in Javanese script literacy demonstrate either high or medium levels of critical thinking abilities. Students who possess limited proficiency in Javanese script exhibit either moderate or poor levels of critical thinking abilities. According to the findings of this study, the researchers suggest that teachers in primary schools utilise script cards in order to facilitate effective learning activities and enhance students' proficiency in Javanese script as well as their critical thinking abilities.